Analisis Tingkat Kemiskinan di Propinsi NTT: Pendekatan Dua Panel - Rosdianawaty Hatta; Rifki Khoirudin (Jurnal Samudra Ekonomi dan Bisnis, 2020)
This study aims to analyze the effect of the human development index, unemployment, economic growth and duration of education on poverty rate of population in the Province of NTT. Secondary data used in the form of time series for the period 2011-2017 and cross sections for 22 city/regency of NTT. Eviews 9 is used to analyze the panel data. The results showed the human development index had a negative and significant effect on poverty rate; unemployment rate has a positive but unsignificant effect on poverty rate; economic growth has a negative but unsignificant effect on poverty rate; and, duration of education has a positive and significant effect on poverty rate. Simultaneously, the four independent variables have a significant effect on poverty. The determination analysis stated that the independent variables used have a relatively large ability to explain changes that occur in the poverty rate of the population in NTT Province.